(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Accounting disclosure is the main means and effective tool for communicating business results to users in support of their decisions, especially those with thought and specialization from academics and professionals in the field of accounting and auditing about the importance of accounting disclosure and transparency in financial reports. Contingent liabilities represent commitments based on the occurrence of one or more events in the future to confirm the value due, the party entitled to it, the maturity date, or to confirm the existence of the obligation itself, and therefore they should not be recognized as a contingent liability in the financial statements and are disclosed only as contingent liabilities. The study aims to identify the basic elements necessary for the disclosure of potential liabilities and contingent liabilities and its trends in the financial reports of the National Insurance Company. The research problem is represented in the difficulty of accounting disclosure of potential liabilities and contingent liabilities for insurance activities, which affected the reliability of the financial statements. A question arises about how to estimate potential liabilities and contingent liabilities in insurance companies and whether they are disclosed in the financial statements. The researchers recommend that it is necessary to hold training courses for employees of insurance companies and employees of auditing companies and offices to familiarize them with international accounting standards in general and financial reporting standard (17) for the insurance industry to develop Applications of accounting disclosure of potential liabilities and contingent liabilities for insurance activities.